2015
DOI: 10.1007/s10896-015-9793-8
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation, Race, and Trauma as Predictors of Sexual Assault Recovery

Abstract: Sexual minorities and racial minorities experience greater negative impact following sexual assault. We examined recovery from sexual assault among women who identified as heterosexual and bisexual across racial groups. A community sample of women (N = 905) completed three yearly surveys about sexual victimization, recovery outcomes, race group, and sexual minority status. Bisexual women and Black women reported greater recovery problems. However, Black women improved more quickly on depression symptoms than n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
101
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 55 publications
(72 reference statements)
5
101
0
1
Order By: Relevance
“…This pattern of results is consistent with and builds upon past research on sexual minority sexual assault survivors (Long et al, 2007; Sigurvinsdottir & Ullman, in press). It is vital to better investigate how multiple victimization experiences impact recovery for survivors as well as whether such patterns of revictimization and their effects vary according to sexual orientation.…”
Section: Discussionsupporting
confidence: 89%
“…This pattern of results is consistent with and builds upon past research on sexual minority sexual assault survivors (Long et al, 2007; Sigurvinsdottir & Ullman, in press). It is vital to better investigate how multiple victimization experiences impact recovery for survivors as well as whether such patterns of revictimization and their effects vary according to sexual orientation.…”
Section: Discussionsupporting
confidence: 89%
“…Black women who identified as LGBQA reported increased traumatic stress symptoms. Some research has found that intersecting experiences of racism, sexism, and heterosexism are associated with higher prevalence of traumatic experiences and negative mental health outcomes for sexual minority women of color (Sigurvinsdottir & Ullman, 2016;Szymanski & Meyer, 2008;Velez, Moradi, & DeBlaere, 2015). Our finding contributes to the literature on sexual minority women of color and their experiences with multiple forms of discrimination and trauma.…”
Section: Discussionsupporting
confidence: 53%
“…The experiences of IPV and/or SA have been shown to have significant health effects, as well as to disproportionately affect women of color (Sigurvinsdottir & Ullman, 2016). It is therefore critical to the health of university-affiliated women of color that colleges and universities provide culturally competent responses to IPV and/or SA.…”
Section: Discussionmentioning
confidence: 99%